Factors influencing patient decision of choosing type of treatment for improvement of dental aesthetics - Gržić, Renata; Gržić, Renata; Špalj, Stjepan; Lajnert, Vlatka; Glavičić, Snježana; Uhač, Ivone; Kovačević Pavičić, Daniela (Vojnosanitetski pregled, 2017)
Objectives: The purpose of this research was to investigate factors influencing patient decision of choosing type of treatment for improvement of dental aesthetics.Material and methods: A total of 700 Caucasian subjects participated in the cross-sectional study (261 men, 439 women, aged 18-86 years, mean age 46.2±18.6). Study included clinical examination and self-administrated questionnaire based on self-perceived aesthetics, satisfaction with the appearance of their maxillary anterior teeth and previous dental experience. Multiple logistic regression was used in statistical analysis.Results: Hiding teeth during smile was the most important predictor for choosing fixed prosthetic restorations (OR 9.1), followed by self-perceived bad fixed prosthesis, malpositioned teeth and female gender (OR 2.9, 2.4, and 1.5, respectively). The increase of satisfaction with dental appearance and previous orthodontic therapy reduced chances for seeking prosthetic therapy (each OR 0.4). The significant predictors for choosing bleaching were hiding teeth during smiling, already done bleaching, female gender, lower levels of satisfaction with dental appearance and the absence of the previous orthodontic therapy (OR 5.8, 2.4, 1.8, 0.5 and 0.4, respecitively). Hiding teeth during smile, self-perceived malposition and crowding, and lower levels of satisfaction, were significant predictors for choosing orthodontic treatment (OR 3.1, 2.4, 2.2 and 0.6, respectively). None of current dental statuses was statistically significant predictor for choosing prosthodontic, bleeching nor orthodontic therapy. Conclusion: The psychological elements and female gender are main predictors of seeking dental therapy. Understanding the prevalence of dissatisfaction of present esthetic and desired treatments for the improvement of esthetics can be a guide for strategies for intervention to improve esthetics.